Efeito da heterogeneidade da paisagem sobre redes de interações plantas-polinizadores - Tokumoto, Paola Mandetta [UNIFESP] (2015)
Most studies about the effects of anthropogenic landscape changes on biodiversity have focused on parameters such as species richness and abundance. Few are those that aim to understand the effects of these disturbances on ecological processes such as pollination, which are important for the maintenance of natural and anthropic ecosystems. Pollinating insects are sensitive to changes in the landscape, what may be one of the leading forces for the global decline of these organisms. In this context, the analysis of plant-pollinators interaction networks allows us to better understand the resistance and resilience of pollination processes against landscape changes. Recent studies show that the abundance and richness of pollinators and agricultural productivity tend to be higher in landscapes that are more heterogeneous and with greater amount of forest. However, there is a necessity to better understand how different types of environments affect plant-pollinator interaction networks with a functional approach. This study evaluated the influence of functional heterogeneity of the landscape on plant-pollinator interaction networks, on the richness and abundance of insect flower visitors, and the richness of flowers available in Atlantic Forest fragments. Our main hypothesis was that in more diverse, forested, connected and with higher quality landscapes, we should find more resistant and resilient plant-pollinator interaction networks, as well as richer flower and pollinator communities. For this, we selected 12 landscapes, within a gradient of landscape diversity and forest proportion. In each central forest fragment, we actively collected floral visitors and flowering plants to build plant-pollinator networks for each landscape. We analyzed our data using a multiple competing hypotheses model selection approach based on the Akaike Information Criterion - AIC. Pollinator communities were richer and more abundant in landscapes with higher proportion of forest; more asymmetrical in landscapes with greater functional connectivity; more modular in better quality and more diverse landscapes; and with greater diversity of interactions in landscapes with higher quality and proportion of forest. In studies that aim to understand how landscape changes affect pollination in realistic scenarios, it is important to consider, in addition to the amount of forest, how the composition and configuration of different environments in landscape affect this ecological process.